The use of lexical phrases by the third-year mainstream students in speaking classes at Faculty of English language teacher eduation, University of Languages and International Studies, Vietnam National University, Hanoi - Trịnh, Thị Diep (2020)
The research paper is expected to find out typical categories of lexical phrases used by the third year mainstream students in speaking classes at FELTE, ULIS, VNUH and their attitudes towards using these lexical phrases. The aims are presented in two questions below: 1. What are typical categories of lexical phrases used by the third year mainstream students in speaking classes at FELTE, ULIS, VNUH? 2. What are the third year mainstream students‟ attitudes towards using lexical phrases in speaking classes at FELTE, ULIS, VNUH?